Associated factors for post-partum weight retention in adolescent mothers: a prospective study (Research, Society and Development, 2022)
Objective: To assess weight retention in adolescent mothers at the fourth postpartum month and its association with sociodemographic, reproductive, anthropometric and behavioral factors. Methods: Prospective longitudinal study. The survey was conducted in all public and private maternity hospitals in a city in the east of Minas Gerais State. All adolescent mothers (age